Preparation and application of filtering type super-hydrophilic / underwater super-oleophobic material for efficient emulsion separation

By growing iron oxide -like structures on the surface of the metal rubber surface and attached to the silicon nanoparticles to form a dual -dimensional composite structure, the problem of poor mechanical performance of super -proof water/underwater ultra -oil material mechanical properties, realizing corrosion resistance, durability and durability and Effect of high -efficiency emulsion separation.

CN119345751AActive Publication Date: 2025-01-24FUZHOU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411710078.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-01-24
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The existing ultra-hydrophilic/underwater superoleophobic materials have poor mechanical properties and are prone to damage, which limits their stability and durability in practical applications, especially inefficient during emulsion separation.

Method used

By self-growing an iron oxide flake structure on the surface of the metal rubber and attaching zero-dimensional spherical hydrophilic silica nanoparticles, a two-dimensional composite structure is formed to improve the material's mechanical strength and emulsion separation performance.

Benefits of technology

A filter -resistant, durable, and good emulsion separation performance has been realized. performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119345751A_ABST
    Figure CN119345751A_ABST
Patent Text Reader

Abstract

The invention discloses preparation and application of a filtering type super-hydrophilic / underwater super-oleophobic material for efficient emulsion separation. The material is prepared by the following steps: taking metal rubber obtained by stamping as a substrate, soaking the substrate in a ferric chloride solution, adding a sodium borohydride solution so as to self-grow an iron oxide nano-sheet structure on the surface of the substrate, soaking the substrate in a nano-silicon dioxide dispersion liquid prepared by a sol-gel method, and drying, thereby obtaining the nano-silicon dioxide / iron oxide composite material. A nano silicon dioxide particle micro-convex structure is formed on the surface of the material through combination and then is heated and cured, so that the overall surface roughness of the material is obviously improved, and the wear resistance, corrosion resistance and stability of the material are obviously improved; the obtained super-hydrophilic / underwater super-oleophobic material has efficient oil-water emulsion separation performance, lasting super-hydrophilic / underwater super-oleophobic stability and excellent mechanical stability and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of superwetting materials, and in particular relates to the preparation and application of a filtering superhydrophilic / underwater superoleophobic material for efficient emulsion separation. Background Art

[0002] Common oily wastewater is mainly divided into three types: laminar oil-water, dispersed oil, and oil-water emulsion (oil-in-water emulsion and oil-in-water emulsion). Among them, the particle size of oil-water emulsion is the smallest (<20μm). At the same time, due to the presence of surfactants, the chemical properties of emulsified oil are more stable, which poses a greater challenge to its separation. In view of this, the development of oil-water separation technology is particularly urgent. Most of the current separation technologies have problems such as long time consumption and low efficiency, and innovative and efficient solutions are urgently needed. In this context, the development of advanced emulsion separation materials is particularly important. In particular, superhydrophilic / underwater superoleophobic materials with low surface energy and high surface roughness. However, the surface microstructure of this type of material is extremely sensitive to mechanical wear and impact, and is easily damaged, which limits its stability and durability in practical applications. Therefore, how to improve the mechanical strength and environmental adaptability of superhydrophilic / underwater superoleophobic materials is a key issue that needs to be solved in current research.

[0003] Metal rubber is a homogeneous porous material with elasticity. The wire winding machine winds the metal wire into a blank with a pitch spiral according to a certain rule, and then cold stamps it in the mold. With its excellent mechanical properties, such as vibration damping, sound insulation and noise reduction, and throttling sealing, it is widely used in aerospace, automobiles and ships, land weapons, flame retardant and explosion-proof devices and other fields. The raw materials and processing technology of metal rubber give it a three-dimensional mesh structure. By controlling different molding pressures and wire diameters, its porosity and dirt holding capacity can be changed. It has the advantages of high bearing capacity and long service life. Compared with other filter materials, it can play an incomparable advantage in harsh environments such as aerospace, national defense equipment, and special working conditions. Therefore, the research on wear-resistant and durable adsorption-type oil-water emulsion separation composite materials based on metal rubber is of great value in protecting the environment and recycling oil. Summary of the invention

[0004] In view of the above problems, the purpose of the present invention is to give metal rubber super-hydrophilic properties through a preparation process based on bionic super-hydrophilic materials, thereby preparing a filtering super-hydrophilic / underwater super-oleophobic material that is corrosion-resistant, durable and has good emulsion separation performance.

[0005] To achieve the above object, the present invention adopts the following technical solution: A highly efficient emulsion separation filtering superhydrophilic / underwater superoleophobic material is based on metal rubber, on the surface of which self-grown iron oxide flake structures are attached with zero-dimensional spherical hydrophilic silicon dioxide nanoparticles.

[0006] The preparation method of the filtering type super hydrophilic / underwater super oleophobic material comprises the following steps: a) Winding the metal wire into a spiral coil through a wire winding machine; b) placing the spiral roll in a metal mold, using staged stamping to form a metal rubber, and then ultrasonically cleaning and drying it for later use; c) adding solid ferric chloride hexahydrate into deionized water and stirring to prepare a ferric chloride solution; d) adding sodium borohydride into deionized water and stirring to prepare a sodium borohydride solution; e) adding an ethanol solution of tetraethyl orthosilicate (TEOS) to an ethanol / water solution of aqueous ammonia, and adding polyvinylpyrrolidone (PVP) as a dispersant, and stirring to form a mixed solution; f) placing the cleaned metal rubber in step b) into the ferric chloride solution prepared in step c) and stirring for a certain period of time, then dropping the sodium borohydride solution prepared in step d) into the solution, continuing to stir for a certain period of time, taking it out, vacuum drying it, and then placing it into the mixed solution prepared in step e) and soaking it for a certain period of time; g) taking out the material prepared in step f), and putting it into a vacuum muffle furnace for curing and drying, thereby obtaining the filtering type super hydrophilic / underwater super oleophobic material.

[0007] Furthermore, the material of the metal wire in step a) includes stainless steel, aluminum alloy, high carbon steel, copper alloy, titanium alloy, and its diameter is 0.12-0.3 mm.

[0008] Furthermore, the spiral coil obtained in step a) has a pitch of 0.8-2.2 mm and a porosity of 20-40%.

[0009] Furthermore, the shape of the metal mold in step b) includes a cylinder, a cuboid, a cube, a sphere, an ellipsoid, a prism, and a three-dimensional ring.

[0010] Furthermore, the specific operation of the staged stamping in step b) is: stamping downwards to a predetermined height at a speed of 3 mm / min on a stamping machine and maintaining the height for 1.5 min.

[0011] Furthermore, the diameter of the metal rubber obtained in step b) is 24 mm.

[0012] Furthermore, the ultrasonic cleaning time in step b) is 15 minutes.

[0013] Furthermore, the concentration of the ferric chloride solution obtained in step c) is 0.43 g / 20 mL.

[0014] Furthermore, the concentration of the sodium borohydride solution obtained in step d) is 0.03 g / 10 mL.

[0015] Furthermore, the mass ratio of tetraethyl orthosilicate, ammonia water and polyvinyl pyrrolidone used in step e) is 2:100:1; and the volume ratio of ethanol to water in the ethanol / water solution of ammonia water is 4:3.

[0016] Furthermore, in step f), the metal rubber is placed in a ferric chloride solution and stirred for 15 minutes, and then the sodium borohydride solution is dropped into the solution and stirred for 45 minutes, and then the solution is immersed in the mixed solution for 30 minutes.

[0017] Furthermore, in step g), the curing and drying is performed at a temperature of 120° C. and for 30 minutes.

[0018] The filtration-type superhydrophilic / underwater superoleophobic material can be used for separation of oil-in-water emulsions.

[0019] Furthermore, the applicable oil phase is one or more of n-hexane, petroleum ether, 1,4-dimethylbenzene, 1,2-dichloroethane and toluene.

[0020] The preparation process of the material in the present invention does not need to use any binder, mainly using iron oxide flakes combined with nano spherical silica particles to form a two-dimensional composite structure of the rough structure itself and hydrophilic high surface energy characteristics, so that the problem of material separation performance degradation caused by swelling of the adhesive when separating the emulsion for a long time can be avoided, and secondary damage to the environment can be avoided. At the same time, the two-dimensional composite irregular structure formed by the iron oxide flakes combined with the nano spherical silica particles in the material of the present invention forms a three-dimensional super hydrophilic / underwater super oleophobic layer with the metal rubber. In addition to intercepting the oil droplets in the water-in-oil emulsion, its internal cross-entangled structure can also serve as an oil pipeline, accelerate the separation efficiency of the emulsion, and greatly enhance the stability and mechanical properties of the overall composite material.

[0021] The present invention has the following advantages: (1) In view of the shortcomings of superhydrophilic materials such as poor mechanical properties and poor wear resistance, the present invention, in the process of preparing metal rubber, weaves the metal wire into a spiral coil by winding, and eliminates the residual preload of the material by staged stamping; then the obtained metal rubber is stirred in a ferric chloride solution and dripped with a sodium borohydride solution for stirring, and then immersed in a nano-silicon dioxide dispersion solution, and finally dried and solidified in a vacuum muffle furnace to prepare a filtration-type superhydrophilic / underwater superoleophobic material with corrosion resistance, durability and good emulsion separation performance. The formula of the present invention is scientific and reasonable, and the process flow is simple and practical. The obtained material can be used for the recovery of leaked oil at sea and the treatment of daily oily wastewater, and has extremely high environmental protection value and broad application space.

[0022] (2) The present invention uses metal rubber as a substrate to prepare a filtering superhydrophilic / underwater superoleophobic material with excellent mechanical properties, corrosion resistance, durability and good emulsion separation performance. Among them, the metal rubber has the characteristics of wear resistance, vibration resistance, high temperature resistance, etc., and has a uniform cross-porous structure, providing an excellent metal frame. The iron oxide sheet and the hydrophilic nano-silicon dioxide spherical composite structure grow and adhere on the metal rubber wire to form a surface roughening modification, which greatly improves the emulsion separation ability of the metal rubber, so that it can separate a variety of water-in-oil emulsions, especially the difficult-to-separate water-in-oil emulsions formed by the emulsified lubricating oil and anti-wear oil produced in the aviation machinery system and mixed with water. At the same time, the superwetting material is compounded on the metal rubber with a relatively high porosity structure, which improves the mechanical properties, durability and stability of the superwetting material.

[0023] (3) The present invention in situ grows iron oxide flakes combined with nano-spherical silica particles on the metal rubber wire to form a two-dimensional composite structure, which makes the material have superior high surface energy and hydrophilic and oleophobic wettability. In addition, since the filter material is a three-dimensional material with multi-pore and multi-connectivity characteristics, it can also separate water-in-oil emulsions with complex components and high viscosity, such as cutting oil and anti-wear oil in mechanical processing, as well as cosmetic oil and food oil in daily life. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Actual pictures and SEM microscopic images of the metal rubber MR (a, e) obtained by stamping and the filtering superhydrophilic / underwater superoleophobic material P-MRFS (bd, fg) prepared in the example.

[0025] Figure 2 This is the EDS spectrum of the filtering super hydrophilic / underwater super oleophobic material P-MRFS prepared in the example.

[0026] Figure 3 SEM images and XPS spectra of the metal rubber MR (a) obtained by stamping and the filtering superhydrophilic / underwater superoleophobic material P-MRFS (b) prepared in the example.

[0027] Figure 4 The corrosion resistance test diagram of the filter-type metal rubber super-hydrophilic / underwater super-oleophobic material P-MRFS prepared in the embodiment. Among them, a is the Tafel curve of metal rubber MR and P-MRFS under acid-base salt environment test, b is the underwater oil contact angle photo of P-MRFS after being placed in deionized water and acid-base salt environment for 48 hours, c is the contact angle change curve of P-MRFS placed in deionized water and acid-base salt environment for 48 hours, and d is the oil-water separation efficiency of P-MRFS after being placed in acid-base salt environment for 1, 3, and 7 days.

[0028] Figure 5The wear resistance performance diagram of the filter-type superhydrophilic / underwater superoleophobic material P-MRFS prepared in the embodiment. Among them, a is a schematic diagram of the friction performance experiment, b is a schematic diagram of the underwater oil contact angle of P-MRFS after the friction distance is 0cm, 200cm, and 400cm, c is the underwater oil contact angle and underwater oil rolling angle of P-MRFS within a friction distance of 400cm, and d is the flux of P-MRFS for various water-in-oil emulsions after the friction distance is 400cm and the water purity after separation.

[0029] Figure 6 This is an emulsion separation performance diagram of the filter-type super-hydrophilic / underwater super-oleophobic material P-MRFS prepared in the embodiment. Among them, a is a diagram of the oil-water separation device, b is an optical microscope diagram of the oil-in-water emulsion and the filtrate before and after the separation of five oil-in-water emulsions, c is a particle size distribution diagram before the separation of five oil-in-water emulsions, d is a particle size distribution diagram after the separation of five oil-in-water emulsions, e is the underwater oil contact angle value for five oil-in-water emulsions, f is a separation flux and separation efficiency diagram for five oil-in-water emulsions, and g is a flux and efficiency change diagram of n-hexane for emulsion separation cycle.

[0030] Figure 7 These are the emulsion separation performance diagrams of materials P-MRF (a) and P-MRS (b) prepared in Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0031] A filtering super-hydrophilic / underwater super-oleophobic material for efficient emulsion separation, the preparation of which comprises the following steps: a) Winding the metal wire into a spiral coil through a wire winding machine; b) placing the spiral roll in a metal mold, using staged stamping to form a metal rubber with a diameter of 24 mm, ultrasonically cleaning it with ethanol and deionized water for 15 minutes each, and then drying it for later use; c) adding solid ferric chloride hexahydrate to deionized water and stirring to prepare a 0.43 g / 20 mL ferric chloride solution; d) adding sodium borohydride to deionized water and stirring to prepare a 0.03 g / 10 mL sodium borohydride solution; e) adding an ethanol solution of tetraethyl orthosilicate (TEOS) to an ethanol / water solution of ammonia (4:3, v / v), adding polyvinyl pyrrolidone (PVP) as a dispersant, and stirring to form a mixed solution; f) placing the cleaned metal rubber in step b) into the ferric chloride solution prepared in step c) and stirring for 15 minutes, then dropping the sodium borohydride solution prepared in step d) into the solution, stirring for 45 minutes, taking it out, vacuum drying it, and then placing it into the mixed solution prepared in step e) and soaking it for 30 minutes; g) The material prepared in step f) is taken out, placed in a vacuum muffle furnace, and cured and dried at 120° C. for 30 min to obtain a filtration-type super-hydrophilic / underwater super-oleophobic material.

[0032] The metal wire in step a) is made of stainless steel, aluminum alloy, high carbon steel, copper alloy, titanium alloy, and has a diameter of 0.12-0.3 mm. The pitch of the spiral coil is 0.8-2.2 mm, and the porosity is between 20-40%.

[0033] The shape of the metal mold in step b) includes a cylinder, a cuboid, a cube, a sphere, an ellipsoid, a prism, and a three-dimensional ring. The specific operation of the staged punching is: punching down to a predetermined height at a speed of 3 mm / min on a punching machine and maintaining it for 1.5 minutes.

[0034] The mass ratio of tetraethyl orthosilicate, aqueous ammonia and polyvinyl pyrrolidone used in step e) is 2:100:1.

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0036] (1) A metal wire with a diameter of 0.1 m is wound into a spiral coil with a pitch of 1.5 mm and a porosity of 20-40% by a wire winding machine; (2) 5 g of the spiral roll was placed in a cylindrical metal mold and stamped into a cylindrical metal rubber with a diameter of 24 mm by staged stamping. The cylindrical metal rubber was ultrasonically cleaned with ethanol and deionized water for 15 min each and then dried for later use; (3) Add 0.43 g of solid ferric chloride hexahydrate to 20 ml of deionized water and stir to prepare a ferric chloride solution; (4) Add 0.15 g of sodium borohydride to 50 ml of deionized water and stir to prepare a sodium borohydride solution; (5) Using the sol-gel method, 11.43 mL of a 25 vol% ethanol solution of tetraethyl orthosilicate (TEOS) was added to 6.42 mL of an ethanol / water solution (4:3, v / v) containing 2.15 mL of aqueous ammonia, and the mixture was stirred to prepare a mixed solution. During the stirring process, 0.2% polyvinyl pyrrolidone (K30) was added as a dispersant. (6) placing the prepared metal rubber in a ferric chloride solution and stirring for 15 minutes, then dropping a sodium borohydride solution into the solution, stirring for 45 minutes, taking it out, vacuum drying it for 30 minutes, and then placing it in the mixed solution prepared in step (5) and soaking it for 30 minutes; (7) The material prepared in step (6) was taken out and placed in a vacuum muffle furnace at 120° C. for vacuum drying for 30 min to obtain a filtration-type superhydrophilic / underwater superoleophobic material, which was labeled as P-MRFS.

[0037] Comparative Example 1 (1) A metal wire with a diameter of 0.1 mm is wound into a spiral coil with a pitch of 1.5 mm and a porosity of 20-40% by a wire winding machine; (2) 5 g of the spiral roll was placed in a cylindrical metal mold and stamped into a cylindrical metal rubber with a diameter of 24 mm by staged stamping. The cylindrical metal rubber was ultrasonically cleaned with ethanol and deionized water for 15 min each and then dried for later use; (3) Add 0.43 g of solid ferric chloride hexahydrate to 20 ml of deionized water and stir to prepare a ferric chloride solution; (4) Add 0.15 g of sodium borohydride to 50 ml of deionized water and stir to prepare a sodium borohydride solution; (5) Place the prepared metal rubber in the ferric chloride solution and stir for 15 minutes, then drop the sodium borohydride solution into it, continue stirring for 45 minutes, then take it out and vacuum dry it for 30 minutes; (6) The material prepared in step (5) was taken out and placed in a vacuum muffle furnace at 120° C. for vacuum drying for 30 min. The obtained material was labeled as P-MRF.

[0038] Comparative Example 2 (1) A metal wire with a diameter of 0.1 mm is wound into a spiral coil with a pitch of 1.5 mm and a porosity of 20-40% by a wire winding machine; (2) 5 g of the spiral roll was placed in a cylindrical metal mold and stamped into a cylindrical metal rubber with a diameter of 24 mm by staged stamping. The cylindrical metal rubber was ultrasonically cleaned with ethanol and deionized water for 15 min each and then dried for later use; (3) Using the sol-gel method, 11.43 mL of a 25 vol% ethanol solution of tetraethyl orthosilicate (TEOS) was added to 6.42 mL of an ethanol / water solution (4:3, v / v) containing 2.15 mL of aqueous ammonia, and the mixture was stirred to prepare a mixed solution. During the stirring process, 0.2% polyvinyl pyrrolidone (K30) was added as a dispersant. (4) Soaking the prepared metal rubber in a 4 mg / mL dopamine solution for 24 hours, and then soaking it in the mixed solution prepared in step (3) for 30 minutes; (5) The material prepared in step (4) was taken out and placed in a vacuum muffle furnace at 120° C. for vacuum drying for 30 min. The obtained material was labeled as P-MRS.

[0039] Figure 1 The physical pictures and SEM microscopic electron microscope pictures of the metal rubber MR obtained by stamping and the filtering super hydrophilic / underwater super oleophobic material P-MRFS prepared in this embodiment. It can be seen from the figure that the surface of the original metal rubber is smooth without any rough structure (e), while in P-MRFS, iron oxide sheets are combined with nano-spherical silica particles to form a two-dimensional composite irregular structure, and are evenly distributed on the surface of the metal rubber material (d, h). In addition, by comparing the illustrations in e, f, and h, it can be seen that from the wettability level, compared with the super hydrophilicity / oleophilicity of MR in the air (both reaching 0°), P-MRFS has excellent underwater super oleophobicity (UWOCA reaches 0° and 156°).

[0040] Figure 2 This is the EDS spectrum of the filter-type super-hydrophilic / underwater super-oleophobic material P-MRFS prepared in this example. The EDS results show that the material surface contains Fe, Si, C, O and N elements.

[0041] Figure 3 The SEM image and XPS spectrum of the metal rubber MR (a) obtained by stamping and the filtering super hydrophilic / underwater super oleophobic material P-MRFS (b) prepared in this embodiment. The figure shows the coexistence of elements Fe, Si, O, C and N in P-MRFS. Among them, the increase in the main peaks of Fe, Si, N and O elements indicates the successful attachment of iron oxide sheets and the successful attachment of silicon dioxide nanoparticles. At the same time, the appearance of Fe2P1 in the figure indicates the existence and generation of iron oxide and ferrous oxide, which further proves that the composition of the nanosheet structure is mainly a composite composition of iron oxide and ferrous oxide.

[0042] The corrosion resistance experiment was conducted using metal rubber MR and filter-type superhydrophilic / underwater superoleophobic material P-MRFS. The specific operation is to immerse the metal rubber MR and P-MRFS in acid, alkali and salt corrosive solutions, measure their 3.5wt% NaCl solution, NaOH (pH=13) solution and HCl (pH=2) solution and the corresponding potentiodynamic polarization curves, and use the electrochemical workstation to analyze the corrosion potential (Ecorr) and corrosion current density (Icorr) of the samples by Tafel extrapolation method. The results are shown in Figure 4 And Table 1.

[0043] Table 1 Corrosion resistance characterization data of MR and P-MRFS

[0044] Generally, high corrosion potential and low corrosion current density mean that the material has good corrosion resistance. The results in Table 1 show that under three different corrosion environments, the corrosion potential of P-MRFS is larger than that of metal rubber MR, and the corrosion current density of P-MRFS is smaller. Therefore, it is proved that P-MRFS has higher corrosion resistance. Combined with the analysis of electron microscopy results, it can be seen that the surface of P-MRFS is covered with a uniform flaky metal iron oxide structure and a large amount of spherical silica material is attached to the surface of the flaky structure. Since silica itself has strong corrosion resistance and stability, it will accommodate more air and form an air film between the corrosive liquid and the corrosive liquid, thereby reducing the corrosion area and improving the corrosion resistance. At the same time, the three-dimensional framework based on metal rubber can avoid direct contact between the inside of the material and the corrosive liquid, which indirectly improves the corrosion resistance of the material.

[0045] At the same time, by Figure 4 The results show that after being immersed in a corrosive environment for 48 hours, the underwater oil contact angle of P-MRFS shows a slight decrease, but it maintains a high oleophobicity of 149° (b, c). Based on the theory of wettability and oil-water separation, such a high underwater oleophobic angle will fully guarantee the acquisition of high separation performance. At the same time, the water-in-oil separation efficiency of P-MRFS after being placed in acid, alkali and salt for 1, 3, and 7 days remained above 99.5% (d). The above shows that P-MRFS has good corrosion-resistant oil-water separation ability.

[0046] The wear resistance test was carried out using the filter-type super-hydrophilic / underwater super-oleophobic material P-MRFS, which specifically involved a friction cycle test of the filter-type super-hydrophilic / underwater super-oleophobic material under a 200g weight. The results are shown in Figure 5 .Depend on Figure 5 It can be seen that with the increase in the number of friction times, the underwater oil contact angle UWOCA gradually increases and eventually tends to a stable value of about 158°, and the underwater oil rolling angle gradually increases and eventually tends to be stable, with a stable value of about 15° (c). At the same time, it can be seen from the electron microscope images before and after wear that during the wear process, the metal rubber provides a solid framework for the flake-like structure. In addition, the flux and water purity of P-MRFS have not changed much after wear, indicating that P-MRFS can still maintain high separation efficiency after surface wear (d). The above shows that P-MRFS has good mechanical durability. At the same time, the three-dimensional framework based on metal rubber can prevent the material from being directly subjected to friction and wear, thereby ensuring the integrity and separation ability of the internal silk composite structure, and indirectly improving the durability of the material.

[0047] The filter-type superhydrophilic / underwater superoleophobic material P-MRFS prepared in the example was used for emulsion separation experiment. The emulsion used was an oil-in-water emulsion of n-hexane, petroleum ether, 1,4-dimethylbenzene, 1,2-dichloroethane and toluene, with a water-to-oil volume ratio of 100:1, and Tween 80, a surfactant stabilizer, was added. The results are shown in Figure 6 .

[0048] Depend on Figure 6 It can be seen that micron-sized water droplets are observed in the lubricating oil, but no water droplets are observed in the filtrate (b). At the same time, the particle size distribution diagrams in the emulsion before separation and the filtrate after separation show that the number of emulsion droplets in the filtrate is significantly reduced compared with the former, indicating that the surfactant-stabilized water-in-oil emulsion has been eliminated (c, d). The underwater oil contact angles of the five water-in-oil emulsions are all above 150° (e), meeting the prerequisite for emulsion separation; and the separation efficiency and flow rate data show that the efficiency can reach more than 99.5% and maintain a large flow rate (f, g), which proves that the filtration-type superhydrophilic / underwater superoleophobic material can efficiently separate water-in-oil emulsions.

[0049] Under the same experimental conditions, the P-MRF and P-MRS prepared in the comparative example were used to carry out oil-water separation experiments on five kinds of water-in-oil emulsions. The results are shown in Figure 7 .Depend on Figure 7 It can be seen that the average separation efficiency of both for the five oil-in-water emulsions is below 90%, which cannot meet the requirements of efficient separation. It can be seen that compared with a single attached material, the separation efficiency and separation flux of P-MRFS are significantly improved.

[0050] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A filtering super-hydrophilic / underwater super-oleophobic material for efficient emulsion separation, characterized in that: The material is based on metal rubber, on the surface of which iron oxide flake structures are self-grown and zero-dimensional spherical hydrophilic silicon dioxide nanoparticles are attached.

2. A method for preparing a filtering super-hydrophilic / underwater super-oleophobic material as claimed in claim 1, characterized in that: The steps include: a) Winding the metal wire into a spiral coil; b) placing the spiral roll in a metal mold, using staged stamping to form a metal rubber, and then ultrasonically cleaning and drying it for later use; c) adding solid ferric chloride hexahydrate into deionized water and stirring to prepare a ferric chloride solution; d) adding sodium borohydride into deionized water and stirring to prepare a sodium borohydride solution; e) adding the ethanol solution of tetraethyl orthosilicate to the ethanol / water solution of aqueous ammonia, adding polyvinyl pyrrolidone as a dispersant, and stirring to form a mixed solution; f) placing the cleaned metal rubber in step b) into the ferric chloride solution prepared in step c) and stirring for a certain period of time, then dropping the sodium borohydride solution prepared in step d) into the solution, continuing to stir for a certain period of time, taking it out, vacuum drying it, and then placing it into the mixed solution prepared in step e) and soaking it for a certain period of time; g) taking out the material prepared in step f), and putting it into a vacuum muffle furnace for curing and drying, thereby obtaining the filtering type super hydrophilic / underwater super oleophobic material.

3. The method for preparing a filtration type super hydrophilic / underwater super oleophobic material according to claim 2, characterized in that: The material of the metal wire in step a) includes stainless steel, aluminum alloy, high carbon steel, copper alloy, titanium alloy, and its diameter is 0.12-0.3 mm; the pitch of the obtained spiral coil is 0.8-2.2 mm, and the porosity is between 20-40%.

4. The method for preparing a filtration type super hydrophilic / underwater super oleophobic material according to claim 2, characterized in that: The shape of the metal mold in step b) includes cylinder, cuboid, cube, sphere, ellipsoid, prism, and three-dimensional ring; the specific operation of the staged stamping is: stamping downward at a speed of 3mm / min on the punching machine to a predetermined height and maintaining it for 1.5min; the diameter of the obtained metal rubber is 24mm.

5. The method for preparing a filtration type super hydrophilic / underwater super oleophobic material according to claim 2, characterized in that: The concentration of the ferric chloride solution obtained in step c) is 0.43 g / 20 mL.

6. The method for preparing a filtration type super hydrophilic / underwater super oleophobic material according to claim 2, characterized in that: The concentration of the sodium borohydride solution obtained in step d) is 0.03 g / 10 mL.

7. The method for preparing a filtration type super hydrophilic / underwater super oleophobic material according to claim 2, characterized in that: The mass ratio of tetraethyl orthosilicate, ammonia water and polyvinyl pyrrolidone used in step e) is 2:100:1; the volume ratio of ethanol to water in the ethanol / water solution of ammonia water is 4:

3.

8. The method for preparing a filtration type super hydrophilic / underwater super oleophobic material according to claim 2, characterized in that: In step f), the metal rubber is placed in a ferric chloride solution and stirred for 15 minutes, and then the sodium borohydride solution is added dropwise and stirred for 45 minutes, and then immersed in the mixed solution for 30 minutes.

9. The method for preparing a filtration type super hydrophilic / underwater super oleophobic material according to claim 2, characterized in that: The curing and drying temperature in step g) is 120° C. and the time is 30 minutes.

10. Use of the filtration-type superhydrophilic / underwater superoleophobic material as claimed in claim 1 in separation of oil-in-water emulsions.

Citation Information

Patent Citations

  • Membrane separation of emulsions produced from hydrocarbon recovery process

    CA2985244A1

  • Preparation and application of anti-wear adsorption type metal rubber composite super-hydrophobic material

    CN115025765A

  • Filter member for oil / water separation

    JP2010155177A

  • Method and apparatus for separation of oil and water using hydrophobic and hydrophilic functional solid particles

    US20130292339A1